2022
DOI: 10.48184/2304-568x-2022-3-151-156
|View full text |Cite
|
Sign up to set email alerts
|

Improving the technology of kefir products with the addition of natural sweeteners stevia

Abstract: In this paper, an analysis of some foreign studies on the use of stevia extract in the production of kefir drinks is given, based on the results of the analysis, a conclusion is summarized about the possibilities of using technologies for adding stevia to kefir products, possible advantages of such production are identified, as well as some disadvantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Recently, a laboratory-scale study was conducted to determine the optimal freeze-drying conditions (Figure 1), with the objective of assessing the stability of camel milk powder and its components under various temperature settings using a freeze-drying method [84,85]. Findings revealed that the resulting camel milk powder exhibited enhanced stability at a humidity level of 11.3%.…”
Section: Prospects For the Production Of Camel Milk Powdermentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a laboratory-scale study was conducted to determine the optimal freeze-drying conditions (Figure 1), with the objective of assessing the stability of camel milk powder and its components under various temperature settings using a freeze-drying method [84,85]. Findings revealed that the resulting camel milk powder exhibited enhanced stability at a humidity level of 11.3%.…”
Section: Prospects For the Production Of Camel Milk Powdermentioning
confidence: 99%
“…In a recent study, a nutritional content of camel milk, including fatty acid and vitamin C profile has been further investigated under spray-drying and freeze-drying technologies [88], [85]. The findings indicated that the production output of milk powder is affected by variables like the feed flows, temperature, and the airflow of the processing apparatus.…”
Section: Prospects For the Production Of Camel Milk Powdermentioning
confidence: 99%